Silicosis Surveillance in California, 2019–2024: Tracking an Epidemic. - Flattery, Jennifer; Woolsey, Chelsea; Fazio, Jane C.; Gandhi, Sheiphali A.; Heinzerling, Amy; Harrison, Robert J.; Cummings, Kristin J. (American Journal of Public Health, 2025)
Objectives. To characterize the nature, burden, and trends of silicosis among California workers, including workers with engineered stone exposures. Methods. We conducted multisource public health surveillance and generated descriptive statistics, compared engineered stone cases to cases with other silica exposures, and examined the utility of various data sources for silicosis surveillance. Results. We received 1817 reports of possible silicosis for 648 individuals from 2019 to 2024 and confirmed 296 (46%) cases, including 243 (82%) associated with engineered stone exposures. Engineered stone cases were more likely to be younger, men, Latino, and from Los Angeles County than were non–engineered stone cases. Of engineered stone cases, at least 15 (6%) were known to have died, and 60 (25%) were referred for lung transplant, including 30 (12%) who received transplants. There was limited overlap between reporting mechanisms. Conclusions. Multisource surveillance was effective for identifying a large number of individuals with silicosis, including people exposed to engineered stone. Outcomes were severe, and many patients had advanced disease. Results illustrate that worker screening and silica exposure mitigation are essential to prevent morbidity and mortality in the engineered stone countertop fabrication industry. (Am J Public Health. 2025;115(11):1913–1921. https://doi.org/10.2105/AJPH.2025.308225)